Advanced strain analysis by high energy synchrotron X-ray diffraction - Korsunsky, A; James, K (Trans Tech Publications, 2002)
Diffraction experiments using high energy, high intensity synchrotron X-ray beams are a powerful method of compiling two or three-dimensional orientation and phase-specific scans of the lattice parameter. This information can be converted into strain and stress maps of high accuracy and resolution, and used for the validation of numerical models of deformation. The present paper describes the use of monochromatic and white beam configurations at ESRF, Grenoble and SRS, Daresbury to study problems of fracture mechanics and plasticity. The characteristic strain variation in the vicinity of the crack front was studied in a nominally single-phase aluminium alloy and is a composite reinforced with SiC particles. Quantitatively, the experimental map of matrix strain in a composite was matched to the LEFM prediction to determine the value of the stress intensity factor. Qualitatively, the transition was clearly identified between the surface and the bulk of a specimen containing a crack. The use of an energy dispersive detector and a white beam is also described to obtain a two-dimensional map of the residual strains in a cross section of a plastically bent beam.